DEVELOPMENT OF A BOOK OF REGULATIONS AND CONDITIONS FOR DORMITORY RESIDENTS BASED ON MORNING SPIRIT - Jovita Ismoerdijahsari Kr; Ibut Priono Leksono; Atiqoh (Institute of Computer Science (IOCS), 2022)
The purpose of this study is to produce a book of rules and regulations as a media to support enforcement of regulations in the UNIPA Surabaya Girls Student Dormitory. This book of rules and regulations is expected to improve the quality of positive behavior for residents of the Unipa Surabaya Girls Dormitory. In the development of the Rules and Orders book, it will be a guideline in enforcing the rules and regulations, so as to create situations and conditions that are good and have character. The development model used in the development of this interactive learning multimedia is the ADDIE model. The ADDIE model is an abbreviation for the five stages of the development process, namely Analysis (analysis), Design (Design), Develop (Development), Implement (Implementation), & Evaluate (Evaluation). The development process involves subject matter experts, learning design experts and learning media experts to provide feedback and suggestions for improvement. The result of this development research is that the product of the Rules and Regulations Book in the Women's Dormitory at PGRI Adi Buana University Surabaya has a material feasibility level of 96.66%, learning design feasibility 88.57%, and learning media feasibility 88.57%. While the small group trial rate is 83% and based on field trials 90% with very feasible qualifications and does not need to be revised.